Effects of Axial Compression and Distraction on Vascular Bud and VEGFA Expression in the Vertebral Endplate of an Ex Vivo Rabbit Spinal Motion Segment Culture Model. Issue 7 (1st April 2021) - Zhan, Jia-Wen; Wang, Shang-Quan; Feng, Min-Shan; Gao, Jing-Hua; Wei, Xu; Yu, Jie; Yin, Xun-Lu; Yin, He; Sun, Kai; Chen, Ming; Xie, Rui; Zhang, Ping; et al.
Abstract : Study Design: An ex vivo study of the rabbit's vertebral endplate. Objective: The aim of this study was to assess the effect of axial compression and distraction on vascular buds and vascular endothelial growth factor (VEGFA) expression of the vertebral endplate (VEP). Summary of Background Data: The abnormal load can lead to intervertebral disc degeneration (IDD), whereas axial distraction can delay this process. The effects of different mechanical loads on the intervertebral disc (IVD) have been hypothesized to be related to changes in the vascular buds of the VEP; moreover, the process that might involve the vascular endothelial growth factor (VEGF) within the VEP. Methods: Rabbit spinal segments (n = 40) were harvested and randomly classified into four groups: Control group, no stress was applied; Group A, a constant compressive load applied; Group B, compression load removed for a fixed time daily on a continuous basis, and substituted with a distraction load for 30 minutes; and Group C, compression removed for 30 minutes for a fixed period daily on a continuous basis. Tissue specimens were collected before the culture (day 0) and on day 14 post-culture of each group for analysis of IVDs' morphology, and protein and mRNA expression of Aggrecan, COL2al, VEGFA, and vascular endothelial growth factor receptor 2 of the VEPs. Results: Application of axial distraction and dynamic load compression significantly delayed time- and constant compression-mediated VEP changes and IDD. Moreover, the degree of degeneration was associated with loss of vascular buds, as well as the downregulation of VEGFA and its receptor. Conclusion: The regulation of vascular buds and VEGF expression in the VEP represents one of the mechanisms of axial distraction and dynamic loading. Level of Evidence: N/A Abstract : Supplemental Digital Content is available in the textAbnormal load-induced intervertebral disc degeneration was related to the vascular bud changes in the VEP. Using an ex vivo model, the study observed the effects of axial compression and distraction on vascular buds and VEGFA expression, and demonstrated that regulation of VEGF in the vertebral endplate represents one mechanism of axial loading.